Land tenurial systems and the adoption of Mucuna planted fallow in the derived savannas of West Africa - Manyong, Victor M.; Houndékon, Victorin A. (International Food Policy Research Institute, 2000)
In 1987, an improved resource management system that incorporates velvet bean (Mucuna pruriens var. utilis) to address soil fertility and weed (Imperata cylindrica) infestation was introduced to the small-scale farmers in a densely populated area of the derived savannas in Benin Republic (West Africa). Six years later, an adoption study was conducted to assess factors driving the adoption process. Four types of land tenure systems based on mode of access to land were identified: divided inheritance, purchasing, gifts, and sharecropping/renting. The first three provide long-term security over land, and together, they represent about 76 percent of the survey fields. Results from three variants of a probit model indicated that security over land was among the factors that significantly affect the adoption of the technology, with a high marginal effect on the probability of adoption, while gender did not have a significant effect. The most important determinant for adoption is the number of times a field is weeded during a cropping season (a proxy for the amount of labor required to tend a crop for better yields). High weeding requirements favorably affect the adoption of velvet bean only if farmers have full security on the degraded (weedy) land. The predominance of land tenure systems that provide secure property rights, namely the traditional acquisition of land through inheritance or gift mode and the gradual development of a land market, facilitated a quick spread of the Mucuna planted fallows in the study region.